Pengaruh Lama Marinasi Dengan Ampas Kopi Arabika Pada Olahan Daging Sapi Terhadap Kualitas Fisik Dan Daya Terima Konsumen - Nabila Putri Pertiwi; Alsuhendra Alsuhendra; Mariani Mariani (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2023)
This research aims to analyze and study the influence of marination with Arabica coffee grounds on processed beef in terms of physical quality and consumer acceptance. The study was conducted at the Laboratory of the Culinary Education Program, Faculty of Engineering, Universitas Negeri Jakarta, from March 22, 2022, to September 25, 2023. The research method employed was experimental. The samples used in this study were processed beef marinated with Arabica coffee grounds for 60 minutes, 90 minutes, and 120 minutes. Subsequently, a panel test was conducted with 30 moderately trained panelists who evaluated predetermined aspects of consumer acceptance. Based on the results of the statistical hypothesis test using Anova for the physical quality test, it was found that there is an influence of marination with Arabica coffee grounds for 60 minutes, 90 minutes, and 120 minutes on the aspect of meat tenderness. According to the results of the statistical hypothesis test for consumer acceptance using the Friedman test, it was found that the texture of processed beef was influenced. Based on the results of the Tukey's test, in terms of product preference for surface color, coffee flavor, meat flavor, texture, coffee aroma, and distinctive meat aroma, the product most preferred from the research was processed beef marinated with Arabica coffee grounds for 120 minutes.